2006
DOI: 10.1007/s00125-006-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of mortality and adverse cardiovascular outcomes in type 2 diabetes: a comparison of patients treated with sulfonylureas and metformin

Abstract: Aims/hypothesis: The aim of this study was to evaluate the risk of adverse cardiovascular outcomes in patients with type 2 diabetes newly treated with sulfonylureas and metformin. Subjects and methods: The Diabetes Audit and Research in Tayside Scotland (DARTS) diabetes information system and the Medicines Monitoring Unit (MEMO) dispensed prescribing database for the population of Tayside, Scotland (400,000 people) were employed. Patients newly prescribed with oral hypoglycaemic agents between 1994 and 2001 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(184 citation statements)
references
References 15 publications
4
171
0
7
Order By: Relevance
“…These results are in agreement with large retrospective analyses. In the survey of Evans et al [18], in spite of similar glycaemic control (HbA 1c~8 %), the mortality rate was lower for metformin than for sulfonylur-eas, with the combination of the two producing an intermediate rate. Among the older adults of the Cardiovascular Health Study [19], a greater mortality rate was observed for those treated with insulin compared with those on oral hypoglycaemic agents, even though there was no apparent difference between these two subgroups in terms of fasting plasma glucose (~10 mmol/l).…”
Section: Different Glucose Medications Different Outcomes?mentioning
confidence: 96%
“…These results are in agreement with large retrospective analyses. In the survey of Evans et al [18], in spite of similar glycaemic control (HbA 1c~8 %), the mortality rate was lower for metformin than for sulfonylur-eas, with the combination of the two producing an intermediate rate. Among the older adults of the Cardiovascular Health Study [19], a greater mortality rate was observed for those treated with insulin compared with those on oral hypoglycaemic agents, even though there was no apparent difference between these two subgroups in terms of fasting plasma glucose (~10 mmol/l).…”
Section: Different Glucose Medications Different Outcomes?mentioning
confidence: 96%
“…In humans, metformin supplementation has been shown to reduce adiposity (40) and mortality rates in diabetic individuals, most effectively in obese and insulin-resistant individuals (41)(42)(43). Although the data so far are promising, further study is needed to show whether metformin is able to extend life span in healthy rodents, primates, and humans.…”
Section: Glucose and Insulin Homeostasismentioning
confidence: 99%
“…In their recent article in Diabetologia, Evans et al demonstrated that the unadjusted risk of cardiovascular mortality with sulfonylurea monotherapy was 3.71 compared with metformin monotherapy [1]. After adjusting for differences between groups, the relative risk of cardiovascular mortality was 1.70 (95% CI 1.18-2.45).…”
Section: To the Editormentioning
confidence: 99%